Communication and Adoption Behavour of Information Technology by Rural Farmers in Ebonyi State - Williams, Egwu Emeka (Asian Journal of Agriculture and Rural Development, 2016)
The study assess the communication method of disseminating agricultural information to rural farmers in Ebonyi State. A multi-stage random sampling technique was used to select respondents. Data analyzed by statistics such as percentage, frequency distribution table and mean score derived from 4-point likert scale. Result show that only 39 percent of the respondents were aware of ADP extension programme while 61 percent were not aware of their existence. The dominant problem to disseminating agricultural information to rural farmers in the study area are: inadequate formal education, lack of infrastructural facilities, lack of interest and aspiration among farmers, introphilly, unaffordable cost of indigenous communication and culture. Based on the research findings, ADP should put move effort in disseminating effective information to enable farmers adopt the new farming technologies that would be profitable and less expensive. Government of Ebonyi State should provide adequate infrastructural materials to the rural areas and encourage more the extension agents to enable them provide adequate information to the rural farmers.